L’évidement de l’image ou la figuration de l’invisible corps du Christ (ixe–xie siècle) - Didier Méhu (Images Re-Vues)
The altar table from the monastery of Saint-Jean-de-Mallast (Montolieu, France, Aude), carved in the middle of the tenth century and now known only through a drawing of Jean Mabillon, presents a unique frame consisting of figures, ornaments and inscriptions around an aniconic field, where one would expect the image of Christ in Majesty. Working with the hypothesis of a deliberate evacuation (“évidement”) of the central image, this paper explores the ways by which the materials of the altar functioned together with the words, images and ornaments carved along the frame to figure not only the invisible body of Christ, but also the processes instigated by the dedication of the church, and finally the celebration of the Eucharist. In a second part, the altar of Montolieu is compared with other examples of pictorial “évidements” seen on eleventh- and twelfth-century liturgical objects and manuscripts.